A Young Case with Endolymphatic Sac Tumors Presented with Right-sided Hearing Loss and Facial Hemi-paralysis - Davoodi, Farzin; Mashayekhi, Mahtab; Khajavi, Mahdi; Mokhtarinejad, Farhad; Khoshsirat, Shahrokh; Rahmani, Zahra; Bazgir, Narges; Naseri, Reza (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Endolymphatic sac tumors (ELSTs) are uncommon low-grade, locally invasive epithelial tumor that originates from the endolymphatic sac of the inner ear and temporal bone. It is a rare event with less than 300 cases worldwide. In this article, we present a case of ELTS who presented with facial asymmetry and hearing loss. In this article, we present a case of ELTS who presented with facial asymmetry and hearing loss. Case presentation: A 15-year-old female was admitted to our hospital with right-sided facial hemiplegia and hearing loss in her right ear which was started and progressed within two years. Except for facial hemiparalysis, other physical examinations were normal. In her audiological investigations, severe hearing loss of her right ear was evident. Imaging studies were indicative of ELSTs. This diagnosis was confirmed by histopathological investigations. Discussion: ELST is an aggressive papillary tumor that arises from the endolymphatic sac. In most cases, this tumor presents as a solitary growth. It usually presents with hearing loss but can be associated with other symptoms like tinnitus, vertigo and nerve VII paralysis. Imaging studies play a crucial role in the diagnosis of ELST, as it can reveal a characteristic soft-tissue mass involving the temporal bone, with bony erosion and extension into adjacent structures. Surgery is considered as the main form of treatment for ELSTs. Conclusion: ELSTs are exceedingly rare events. Here we presented a case of ESLT with right facial hemiplegia and right ear deafness.